2004
DOI: 10.4315/0362-028x-67.2.303
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for Evaluating the Efficacy of Cetylpyridinium Chloride as a Beef Hide Intervention

Abstract: The objective of this study was to establish the necessary protocols and assess the efficacy of cetylpyridinium chloride (CPC) as an antimicrobial intervention on beef cattle hides. Experiments using CPC were conducted to determine (i) the methods of neutralization needed to obtain valid efficacy measurements, (ii) the effect of concentration and dwell time after treatment, (iii) the effect of CPC on hide and carcass microbial populations when cattle were treated at a feedlot and then transported to a processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…The conditions of the EO water washes were demonstrably more effective than those of the ozonated water washes, possibly because of the length of time and/or the application pressure. The liquid pressure at which a hide is washed affects the efficacy of the washing treatment (8). The difference of 0.5 log CFU/100 cm 2 in APC between wash conditions was significant (P Ͻ 0.05), but there was no difference in the EBC or the prevalence of E. coli O157.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The conditions of the EO water washes were demonstrably more effective than those of the ozonated water washes, possibly because of the length of time and/or the application pressure. The liquid pressure at which a hide is washed affects the efficacy of the washing treatment (8). The difference of 0.5 log CFU/100 cm 2 in APC between wash conditions was significant (P Ͻ 0.05), but there was no difference in the EBC or the prevalence of E. coli O157.…”
Section: Resultsmentioning
confidence: 91%
“…The difference of 0.5 log CFU/100 cm 2 in APC between wash conditions was significant (P Ͻ 0.05), but there was no difference in the EBC or the prevalence of E. coli O157. In a previous study in which water was applied to hides at 8,300 kPa (1,200 lb in 2 ) for two 20-s periods, APC were reduced by 0.4 log CFU/100 cm 2 and EBC were reduced by 0.6 log CFU/100 cm 2 (8). Neither of these reductions was significantly different (P Ͼ 0.05) from those for the controls.…”
Section: Resultsmentioning
confidence: 95%
“…E. coli O157:H7 has been a constant concern to the food industry. Various antimicrobial sprays and treatment methods have been employed with partial success to actively reduce the bacterial contamination from beef carcasses and food products (9,25,26,30,45,47,55,59). This study observed that three vital cellular processes, cell division, biofilm formation, and pathogenicity, were all downregulated by FlhC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved to be a highly efficient antimicrobial treatment when applied in the range of 0.5 to 1.2 g liter Ϫ1 (50,88). Nonetheless, ASC has been found to cause physiological damages in fresh produce even when used at concentrations to 1.2 g liter Ϫ1 , allowed by the FDA (31,89).…”
Section: Figmentioning
confidence: 99%